Indonesia Effectiveness Of Filtration System Combinations In Liquid Waste Processing At The Fish Processing Center Of Rumbuk Village, Sakra District: EFEKTIVITAS KOMBINASI SISTEM FILTRASI DALAM PENGOLAHAN LIMBAH CAIR PADA SENTRA PENGOLAHAN IKAN DESA RUMBUK KECAMATAN SAKRA - Widuri, Intan widuri (Fakultas Teknik Universitas Hamzanwadi, 2025)
Fish liquid waste contains high levels of organic matter. A combination processing filtration system consisting of an aerobic biofilter with bioball media and filtration media with gravel, poor sand, palm fiber and pumice stone used in the liquid waste processing process at fish processing centers. This research was conducted to determine the effectiveness of a combination of filtration systems in processing liquid waste from fish processing centers with test parameters for COD, BOD, ammonia and pH. Based on initial tests, fish liquid waste has high parameter values, namely COD 1650 mg/l, BOD 871 mg/l, ammonia 199 mg/l while the pH value is neutral 6.28. Processing using a combination of this filtration system, in the research, was carried out for 13 days in an aerobic biofilter tank and 24 hours in filtration. The research results showed that processing with a combination of filtration systems resulted in a reduction in pollutants with the best values ​​in the 3rd repetition results. COD values ​​were 100 mg/l, BOD 56.6 mg/l, ammonia 102 mg/l and pH 8.87. The effectiveness of processing with a combination of this filtration system is able to reduce COD levels by 93.90%, BOD 93.50% and neutral pH so that it can reach quality standards, while ammonia of 48.74% does not meet the quality standards in Minister of the Environment Regulation No. 5 of 2014 concerning Waste Water Quality Standards for Fishery Product Processing Businesses and/or Activities.